A Cristologia Paulina a partir de Gl 1,1-12: uma abordagem pragmática em diálogo com a Cristologia latinoamericana - Mariano, Rafael Wilian (2022)
Christology stands out as one of the most important theological treatises. Nor could it be otherwise, after all the mystery of Christ - his life, passion, death, resurrection and ascension - occupies the center of the kerygma and, consequently, determines the being of the Church, its practice and its presence in the world. This research examines the Pauline Christology contained in the letter to the Galatians, from Gal 1:1-12. In this pericope, the Apostle makes explicit the first notes of his understanding of the mystery of Christ and demonstrates his concern for the communities of Galatia that are deviating from the authentic Gospel. Paul reaffirms, as the only soteriological mediation, the paschal mystery of Christ, through which he defends the access to salvation for the whole human race. This broad understanding of the Apostle that every human being is reached by salvation in Christ means that "his" Christology can also be applied to the Latin American context. In this Christological dialogue, the centrality of the poor and interculturality occupy a prominent place